(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines theoretical and methodological approaches to the concept of a just state. Various concepts of justice in public administration, their historical development, and modern interpretations are analyzed. Particular attention is paid to legal equality, social well-being, and mechanisms for ensuring justice within the state. Additionally, the authors explore philosophical and political-legal aspects influencing the formation of principles of just governance.